Pengaruh Layanan Penguasaan Konten Teknik Modeling Simbolik Terhadap Penerimaan Diri Siswa - Andini, Ika; Mugiarso, Heru (Indonesian Journal of Guidance and Counseling: Theory and Application, 2016)
Purpose in this research is to test the influence of services guidance mastery content technique modeling symbolic by the video to self acceptance students (self acceptance). Population in this study class viii junior high schools 1 secang consisting of the class viiia-viiif and sample in this research class viiic which consisted of 30 students use purposive sampling. Data collection techniques using psychological scale and observation, using validity with the formula product moment and reliability an instrument with the formula alpha. Data analysis technique be used that is descriptive analysis the percentage and t-test. The result showed the presence of the influence of service content mastery of technique symbolic unified with the media video to an acceptance of students shown with an increase in the self acceptance after these services as much as 14,28 % and testing shows t , indicate its value t-count = 17,442 and t-table = 0,683. Thus the value of t count > t table so that Ha accepted and  Ho rejected. So concluded the service mastery of symbolic modeling techniques with video media has a significant impact on the acceptance of self (self aceptance) students